Evaluasi Maturitas Manajemen Layanan Sistem Informasi Learning NSC Application (LENSA) Menggunakan Framework ITIL Versi 3 Domain Service Operation (Studi Pada Politeknik NSC Surabaya) - Natasya Ekaputri; Yusi Tyroni Mursityo; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Politeknik NSC Surabaya is a private university in Surabaya that organizes education Diploma Program (D3). Politeknik NSC provides some services to students in conducting academic activities every day. Services provided one of them in the form of academic information system. Information systems that have been used intensively by all students is a website that can be accessed via desktop or smartphone. Based on interviews that have been conducted, the information system called Learning NSC Application (LENSA) does not have a good standard of procedure and control mechanism and cause some problems in the use of the system, such as when there is a system error, the handling will be slow. So it is necessary to evaluate the maturity of the system to determine the current level of maturity. This research uses ITIL framework with Service Operation domain. The purpose of this study is to provide recommendations to the agencies of the evaluation that has been done. The result of domain service operation maturity level is 1.87. The recommendation is made to increase the values ​​and reduce the value of expected expectations and can be done through the LENSA information system.